Formulasi dan Uji Efektivitas Sabun Pencuci Tangan dari Ekstrak Daun Pandan (Pandanus amaryllifolius Roxb.) Terhadap Bakteri Salmonella sp. - Vera Estefania Kaban; Nasri N; Hariyadi Dharmawan; Denny Satria (Herbal Medicine Journal, 2022)
Pandan leaf (Pandanus amaryllifolius Roxb.) is a plant that grows wild, which belongs to the Pandanaceae tribe which is used as a natural medicine. The purpose of this study was to determine the antibacterial effectiveness of the handwashing soap formulation of pandan leaf extract against Salmonella sp bacteria and which concentration was the most effective. Extracts were made by maceration method using 96% ethanol as solvent. Formulation with mass 1 and mass 2. Testing of antibacterial effectiveness was carried out by diffusion method using disc paper. The results of the examination of the simplicia characterization of pandan leaves were determined to determine the water content of 0.1575%, the determination of the content of the water soluble extract was 0.1233%, the determination of the concentration of the soluble extract in ethanol was 0.0054%, the determination of the ash content of 0.1575%, the determination of the content of the acid insoluble extract. 0.0101%. Simplicia screening results contain alkaloids, flavonoids, tannins, saponins, and polyphenols. The yield of pandan leaf extraction is 90 g. The results of testing the effectiveness of Salmonella sp antibacterial on the diameter of the most effective inhibition zone was obtained at a concentration of 15% with a diameter of 22.70 mm. The results of the research, it can be concluded that the formulation of hand soap preparations with pandan leaf extract has antibacterial effectiveness against Salmonella sp.